Prospective, Randomized Comparison of Same-Day Dose of 2 Different Bowel Cleanser for Afternoon Colonoscopy: Picosulfate, Magnesium Oxide, and Citric Acid Versus Polyethylene Glycol - Gweon, Tae-Geun; Kim, Sang Woo; Noh, Yong-Sun; Hwang, Seawon; Kim, Na-Young; Lee, Yoonbum; Lee, Soon-Wook; Lee, Sung Won; Lee, Jong Yul; Lim, Chul-Hyun; Hun Kim, Hyung; Kim, Jin Su; et al. (Medicine (Baltimore), 2015)
For afternoon colonoscopy, same-day administration of sodium picosulfate, magnesium oxide, and citric acid (PM/Ca) is recommended. However, few studies have evaluated the bowel-cleansing efficacy and safety of this regimen. The aim of this study was to compare the bowel-cleansing efficacy, side effects, and patient's tolerability of a same-day split administration of PM/Ca with polyethylene glycol (PEG) for afternoon colonoscopy. Patients were randomly assigned to a PM/Ca group or a PEG group. The PM/Ca group consumed 1 sachet of PM/Ca at 06:00 and 1 sachet of PM/Ca 4 hours before the colonoscopy. They also took 2 tablets of bisacodyl before sleep on the night before. The PEG group consumed 2 L of PEG at 06:00 and 2 L of PEG 4 hours before the colonoscopy. All subjects were instructed to finish the bowel cleanser or fluid at least 2 hours before colonoscopy. All colonoscopic examinations were performed in the afternoon on the same day. The bowel-cleansing efficacy was scored using 2 scales: the Ottawa Bowel Preparation Scale (OBPS) and the Aronchick scale. Ease of using the bowel cleanser was rated from 1 (very easy) to 5 (very difficult). Two hundred nine patients underwent colonoscopy. The bowel-cleansing scores by OBPS did not differ between groups (5.0 vs 4.9, P = 0.63). Ease of using the bowel cleanser was superior in the PM/Ca group (P < 0.01). The cleansing efficacy of PM/Ca administered on the day of colonoscopy is comparable to that of PEG. Patients prefer PM/Ca.